THE MEDICAL PERSPECTIVE ON BURNOUT AND ITS IMPORTANCE IN HEALTH CARE WORKERS - Abdul Majeed Muhammad Ali Al-Harbi; Abdul Rahman Salman Al-Ghamdi; Rami Ali Al-Zahrani; Abdul Majeed Ali Al Shehri; Hussain Hassan Al maimouny; Ghayah Mohammed Al-Madawisi; Fahad Naji Mustafa Alkhateeb; Nada Kareem Alenazi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
ObjectiveThe aim of this study was to review recent medical findings related to burnout, its diagnosis, treatment, characteristic pathophysiological features, and preventive measures.Materials and MethodsA systematic review of the scientific literature in PubMed/Medline was performed. The most recent and important findings were reported.ResultsBurnout was found to be a risk factor for myocardial infarction and coronary heart disease. It was also related to reduced fibrinolytic capacity, decreased capacity to cope with stress and hypothalamic-pituitary-adrenal (HPA) axis hypoactivity. Severe burnout symptoms are associated with a lower level or smaller increase of the cortisol awakening response (CAR), higher dehydroepiandrosterone-sulphate (DHEAS) levels, lower cortisol/DHEAS ratios and stronger suppression as measured by the dexamethasone suppression test (DST). More and more literature works suggest that the evaluation of the HPA axis should be brought to the attention of primary care physicians. There is no universal agreement on specific treatment and diagnostic measures to evaluate the wide range of HPA axis disorders. The cost-effective evaluation of adrenal hormones via saliva samples by a primary care physician may significantly alter the course of therapy in numerous chronic disease patients. Psychiatric disorders may have similar symptoms, but they have distinctive hormonal profiles. Having burnout recognized as a medical condition would help in differentiating burnout from similar clinical syndromes, such as depression or anxiety, and provide appropriate treatment to burnout patients. Proper treatment is essential for a fast and full recovery.ConclusionChronic stress-related disorders often fall outside the category of a “true” disease and are often treated as depression or not treated at all. The evaluation of adrenal hormones via saliva samples helps to predict burnout. Burnout screening techniques, dietary and nutritional guidelines and lifestyle changes for supporting the HPA function need to be developed. The presented material includes hormonal, dietary, and pharmaceutical perspectives.